PENGARUH PENGETAHUAN ZAKAT, PENDAPATAN, KEPERCAYAAN, KUALITAS PELAYANAN TERHADAP MINAT APARATUR SIPIL NEGARA (ASN) MEMBAYAR ZAKAT PROFESI MELALUI BAZNAS KABUPATEN DEMAK - Fitriyani, Lailatul; Irkhami, Nafis (Universitas Siliwangi, 2022)
The purpose of this study is to determine the influence of Zakat knowledge, income, trust, and service quality on the interest of State Civil Servants (ASN) to pay professional zakat through Baznas Demak Regency in 2021. The type of research used in this study is field research using a quantitative research approach. The data collection method was carried out through a questionnaire which was distributed to ASNs in the Demak Regency. Samples were taken as many as 100 with the purposive sampling technique. The data obtained then processed using the IMB SPSS 19 tool. This analysis includes the validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, Ftest test, T-test test, and determinant coefficient test (R2). Based on the results of the T-test test, it shows that the variables of Zakat knowledge, income, and service quality have a positive and significant effect on the interest of ASN to pay professional Zakat through Baznas Demak Regency. On the other hand, the trust variable has a positive and insignificant effect on the interest of ASN to pay professional Zakat through Baznas in Demak Regency. The results of the F-test test show that the variables ofÂ Zakat knowledge, income, trust, and service quality together affect the interest of ASN to pay professional Zakat through Baznas in Demak Regency.